Tension‐free vaginal tape‐obturator for the treatment of stress urinary incontinence: a 12‐year prospective follow‐up. (15th October 2018) - Zhang, Ye; Song, Xiaochen; Zhang, Zhibo; Mao, Meng; Ai, Fangfang; Kang, Jia; Zhu, Lan
Abstract : Objective: To evaluate the long‐term safety and effectiveness of inside–out transobturator tape (tension‐free vaginal tape‐obturator, TVT‐O) for the treatment of stress urinary incontinence (SUI). Patients and Methods: Between August 2004 and August 2006, 87 consecutive patients with SUI who underwent TVT‐O were enrolled in this prospective cohort study. Patients with mixed UI, or pelvic organ prolapse requiring surgery, were excluded. Data relating to long‐term postoperative complications, subjective satisfaction rate (Patient Global Impression of Improvement), objective cure rate (stress test), quality of life (QoL), and sexual function, were collected during follow‐up. The Incontinence Impact Questionnaire (IIQ‐7) and Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ‐12) were used to assess QoL and sexual function, respectively. Statistical analyses were performed using paired‐sample t ‐tests. Results: At the 12‐year follow‐up, 73 patients (84%) were available for evaluation. Overall, the long‐term complication rate was 45.2%. De novo overactive bladder was observed in 12.3% of patients. None of the patients reported severe voiding dysfunction that required treatment by tape removal or catheterisation. However, 16 patients (16/73, 21.9%) had voiding changes compared with their preoperative status. Persistent groin pain was reported in 1.4% of the patients, and tape exposure occurred in 5.5%. The subjective satisfaction rate and objective cure rate were 80.8% and 82.2%, respectively. Compared with preoperative scores, the IIQ‐7 score decreased significantly ( P < 0.05), whilst there was no significant difference in the PISQ‐12 score ( P = 0.893). Conclusions: This 12‐year follow‐up study showed that TVT‐O is a highly effective procedure for the treatment of SUI. The long‐term complication rate appears to be slightly high, which should raise concern.